Cupric Halide‐Promoted Stereoselective Intramolecular Cis‐Addition to Construct (Z)‐Chloro(bromo)benzo[c, d]indoles. Issue 35 (15th September 2022) - Diao, Hanying; Liu, Li; Wang, Jin; Lin, Yanfei; Zhao, Xiangyuan; Zeng, Heyang; Shi, Senlei; Gao, Wei; Yang, Long; Du, Guanben; Zhang, Lianpeng
Abstract: A convenient and efficient method for one pot synthesis of polysubstituted ( Z )‐halobenzo[ c, d ]indoles from 8‐alkynyl‐1‐naphthylamine derivatives using CuCl2 and CuBr2 as the halogenated reagents has been developed. In this protocol, both (Z)‐chloro and bromobenzo[ c, d ] indole derivatives can be obtained in moderate to good yields by copper halide‐promoted stereoselective intramolecular cis ‐addition annulation reactions. A novel fluorescent molecule with AIE properties was constructed via Suzuki coupling reaction and its optical properties was investigated, which made them possible candidates for optoelectronic conjugated materials. Abstract : In this paper, we have developed tunable copper‐promoted stereoselective intramolecular cis ‐addition annulation reactions for controllable synthesis of ( Z )‐chloro(bromo)benzo[ c, d ]indoles under mild conditions. A novel fluorescent molecule with AIE properties was constructed by Suzuki coupling reaction using ( Z )‐bromobenzo[ c, d ]indole 3 b as the starting material, and its optical properties was investigated.